The historical sources of language policy - Laitin, David D.; Ramachandran, Rajesh (The journal of politics, 2025)
The designation of an official language is an institutional element of state rationalization, yet factors that determine this choice have not been fully accounted for. This paper provides a framework highlighting two historical factors that are keys to predicting the use of indigenous languages in formal domains: the availability of a written tradition by a major group in the country in the era before missionary and/or colonial exposure and the degree of linguistic fractionalization within the colonially set borders. Statistical estimates test and a set of vignettes illustrate the workings of these historical factors in accounting for postcolonial language policies.
Online veröffentlicht am 10. April 2025
Gesehen am 16.01.2026